Bartik Instruments: What, When, Why, and How - Goldsmith-Pinkham, Paul; Sorkin, Isaac; Swift, Henry (American Economic Review, 2020)
The Bartik instrument is formed by interacting local industry shares and national industry growth rates. We show that the typical use of a Bartik instrument assumes a pooled exposure research design, where the shares measure differential exposure to common shocks, and identification is based on exogeneity of the shares. Next, we show how the Bartik instrument weights each of the exposure designs. Finally, we discuss how to assess the plausibility of the research design. We illustrate our results through two applications: estimating the elasticity of labor supply, and estimating the elasticity of substitution between immigrants and natives. (JEL C51, F14, J15, J22, L60, R23, R32)